2020
DOI: 10.3390/genes11020191
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Candidate Genes Conferring Resistance to Downy Mildew in Maize (Zea mays L.)

Abstract: Downy mildew (DM) is a major disease of maize that causes significant yield loss in subtropical and tropical regions around the world. A variety of DM strains have been reported, and the resistance to them is polygenically controlled. In this study, we analyzed the quantitative trait loci (QTLs) involved in resistance to Peronosclerospora sorghi (sorghum DM), P. maydis (Java DM), and Sclerophthora macrospora (crazy top DM) using a recombinant inbred line (RIL) from a cross between B73 (susceptible) and Ki11 (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
(129 reference statements)
1
6
1
Order By: Relevance
“…Based on previous study, Kim et al (2017) and Ruswandi et al (2015) have identified QTL for downy resistance on chromosome 1 using F2 and BC1F2 populations, respectively. Furthermore, it was also reported by Jampatong et al (2013) that QTL related to Pp in the RILs, Lohithaswa et al (2015) found QTL related to Ps (Peronosclerospora sorghi) in F2 population, and QTL linked Ph (Peronosclerospora heteropogoni) character was obtained BC1F2 population (Kim et al 2020). Based on this study, we conclude that response of 198 F3:4 lines on the DM disease in the field varied from highly resistance to highly succeptible and the DM resistance related QTLs found in present study would give new insight on the future molecular maize breeding program for resistant against downy mildew disease.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Based on previous study, Kim et al (2017) and Ruswandi et al (2015) have identified QTL for downy resistance on chromosome 1 using F2 and BC1F2 populations, respectively. Furthermore, it was also reported by Jampatong et al (2013) that QTL related to Pp in the RILs, Lohithaswa et al (2015) found QTL related to Ps (Peronosclerospora sorghi) in F2 population, and QTL linked Ph (Peronosclerospora heteropogoni) character was obtained BC1F2 population (Kim et al 2020). Based on this study, we conclude that response of 198 F3:4 lines on the DM disease in the field varied from highly resistance to highly succeptible and the DM resistance related QTLs found in present study would give new insight on the future molecular maize breeding program for resistant against downy mildew disease.…”
Section: Discussionsupporting
confidence: 51%
“…In order to obtain a high-density linkage map, therefore, it is suggested that in future work more polymorphic markers between the two adjacent markers are needed to explore. The magnitude of the linkage map formed in this study was about 39.75% of the total maize genome in comparison to the maize genetic map reported by Kim et al (2020).…”
Section: Linkage Map Construction and Qtl Analysiscontrasting
confidence: 49%
See 1 more Smart Citation
“…The results in this study suggested that the crosses between resistant and susceptible varieties showed moderate resistance (Nei9008/BK-24-9-B) and resistance (TY/TF-33-1-B) to downy mildew. Difference in resistance levels among corn varieties is due to polygenic inheritance of resistance [9]. Additive and non-additive effects are equally important in the inheritance of resistance [59].…”
Section: Disease Parametersmentioning
confidence: 99%
“…More recently, two species of DM including Peronosclerospora sorghi and P. maydis have been reported to infect corn in the country [8]. Polygenic inheritance of DM resistance has been reported [9] and additive and non-additive gene effects were equally important in the inheritance of DM resistance in maize [10,11]. Therefore, improvement of small-ear waxy corn genotypes for DM resistance is possible.…”
Section: Introductionmentioning
confidence: 99%